2019
DOI: 10.3390/ani9100835
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a Previously Validated Temperament Test in Shelter Dogs, Including an Examination of the Use of Fake Model Dogs to Assess Conspecific Sociability

Abstract: Simple SummaryGlobally, many unwanted dogs enter rescue shelters. Shelter staff often avail of behavioural tests as an early screening tool to identify areas of concern to minimise the welfare risk associated with long-term kennelling and failed adoptions. A number of requirements need to be verified in order for a test to become a useful assessment tool, including how reliable and accurate the measurements are. For these tools to be widely used, they need to be feasible and reproducible. We refined a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…This is in line with previous studies using fake dogs as proxies for unfamiliar dogs in dog–dog interactions. Barnard et al [ 20 ] found that their subjects responded with the same general behaviors when presented with a fake dog reproduction as with a living dog. Given that the subjects seemed to react (at least initially) to the statue as if it was another dog, it is possible that this stimulus could reflect the response of the tested dog to another unfamiliar dog after being rehomed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous studies using fake dogs as proxies for unfamiliar dogs in dog–dog interactions. Barnard et al [ 20 ] found that their subjects responded with the same general behaviors when presented with a fake dog reproduction as with a living dog. Given that the subjects seemed to react (at least initially) to the statue as if it was another dog, it is possible that this stimulus could reflect the response of the tested dog to another unfamiliar dog after being rehomed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of artificial conspecifics has many advantages, allowing performance of social behavior and cognition experiments in a more controlled and repeatable manner compared to living animals [ 21 , 22 , 23 ]. The use of artificial dogs during behavioral assessments in homes and shelters has gained attention as it permits testing of dogs safely and in a standardized way, although its validity is still controversial [ 20 , 24 , 25 , 26 ]. Future studies should further investigate how dogs perceive social and non-social stimuli and what elements of these stimuli might elicit fear responses.…”
Section: Discussionmentioning
confidence: 99%
“…The items were included to primarily trigger a social response towards people and conspecifics and an exploratory/avoidance response to novel/inanimate objects. We hypothesized that based on previous results with shelter and pet dogs [20,21], responses to some items would reflect specific behavioral characteristics of interest. For example, the ball and squeaky toy previously proved to be a good measure of playfulness, the problem-solving task represented a measure of cognitive flexibility, the artificial dog was a proxy measure of intra-specific sociability, and the leash and commands served as a measure of trainability in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The behavioral component, i.e., a human-approach test, was refined based on previous work [10,17] and thus, needed new examination. The second portion of the assessment was a reactivity test loosely based on previously published work [20,21]. The test was adapted and refined to suit dogs in commercial breeding kennels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation